Actes sexuels, horreur et sorcellerie au cinéma. La copulation avec le Diable : une perspective psychanalytique - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
Sexual Acts, Horror and Witchcraft in Cinema. The Copulation with the Devil: a Psychoanalytical Perspective. This paper tries to approach, taking as a starting point a Romanian painting from the 18th century, a scene with a strong phantasmatic load: the sexual act of a woman, who is considered a witch, with the devil. Several films are analyzed: Häxan by Benjamin Christensen (1922), Rosemary’s Baby by Roman Polanski (1968), L’Anticristo by Alberto de Martino (1974), Angel above, Devil below by Dominic Bolla (1975). These films share some common features, important for the analytical process: the copulation with the devil, the presence of traumatized characters who are submitted to a psychological cure, the recycling of psychoanalytical vocabulary, especially “hysteria”, the problems with parental instances. In order to interpret these films, there is a coming back to Freud’s ideas on the Devil, as expressed in the letters to Wilhelm Fliess or in the study A Seventeenth-Century Demonological Neurosis (1923). The devil as an image of unconscious impulsions or as a substitute of the father are the main Freudian intuitions used here for an optimal interpretation of the chosen films.